2010
DOI: 10.1001/virtualmentor.2010.12.3.medu2-1003
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable International Partnership Building for Academic Medical Centers: Experiences with the Botswana-UPenn Partnership

Abstract: The world faces a global health workforce shortage of almost 4 million professionals, with the most severe gaps in sub-Saharan Africa [1]. Improvements in health, including meeting the health-related Millennium Development Goals, are linked with the density of skilled health workers [2]. In the U.S., the reauthorizing bill for the President's Emergency Plan for AIDS Relief (PEPFAR) requires the U.S. to support training of 140,000 new health workers in PEPFAR focus countries. The participation of U.S. academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Medicine residents pursue individually tailored curriculums in the form of short-term elective rotations at cancer centers in LMICs partnered with a US based institution, such as Botswana – University of Pennsylvania ( 9 ) and Yale/Stanford Johnson & Johnson Global Health Scholars Programs ( 10 ).…”
Section: Current Opportunitiesmentioning
confidence: 99%
“…Medicine residents pursue individually tailored curriculums in the form of short-term elective rotations at cancer centers in LMICs partnered with a US based institution, such as Botswana – University of Pennsylvania ( 9 ) and Yale/Stanford Johnson & Johnson Global Health Scholars Programs ( 10 ).…”
Section: Current Opportunitiesmentioning
confidence: 99%
“…Despite this relatively low count, we found a diversity of internationalization efforts described, including narratives of individual international experiences [ 42 ], research on student initiatives [ 61 ], description of single school programs [ 24 , 25 , 37 , 43 ], institutional partnerships [ 24 , 25 , 67 ], cultural learning at home [ 21 , 30 ], reviews on school websites [ 54 ], and international GH programs [ 32 , 51 ]. As the goal of the study was to determine the current status of IoME in the US via viewing of published literature, the authors identified three overarching themes that summarized the articles, to help in identifying current practices in IoME—institutional partnerships, international learning at home, and student mobility programs.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…With few exceptions, most described reports focused on partnerships between US schools and institutions in the LMICs, the majority in South America and Africa [ 25 27 , 37 , 41 , 56 , 60 , 63 , 67 ], and some in South East Asia [ 34 , 49 ]. Rybak described a partnership with the Ukraine [ 56 ], and there were two reports of the same partnership with Israel [ 26 , 27 ].…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many institutions, establishing partnerships with African institutions for the purposes of learning, scholarship, and/or clinical care is a relatively new undertaking. Models of successful partnerships with formally signed memoranda of understanding have rarely been described in the literature (3537). We speculate that the relative paucity of global health programs in psychiatry may also be related to cultural and/or language barriers to U.S. medical graduates’ practice of psychiatry in non-U.S. settings (12, 14), a challenge that is relatively unique to psychiatry compared to other specialties where greater importance may be placed on procedural aspects of clinical practice.…”
Section: Discussionmentioning
confidence: 99%